ACCOUNTING, REPORTS TO STOCK-HOLDERS, AND THE SEC. - Kaplan, Maurice C.; Reaugh, Daniel M. (The Accounting Review, 1939)
In this article, the author focuses on the adequacy and reliability of corporate accounting reports provided to stockholders and security analysts. He tries to point out the gap in the regulation of accounting reports under Securities Exchange Act, based on around seventy selected corporate balance sheets and income statements for 1937. He also discusses a number of limitations inherent in the accounting material made available to investors. Accountants and investment analysts today are agreed that the income statement is much more significant and informative to the investor than the balance sheet. It reports that the Act applies to corporations with securities listed on national securities exchanges and requires such corporations to file with the Commission and with the exchange annual reports which comply with the standards imposed by the Commission and the exchange. The article undertakes to break additional ground in the inevitably forthcoming critical analysis of accounting categories and accounting concepts.